15 Attenuated heart-brain integration predicts functional non-epileptic seizures. Issue 12 (14th November 2022) - Elkommos, Samia; Martin-Lopez, David; Koreki, Akihiro; Jolliffe, Claire; Mula, Marco; Critchley, Hugo; Edwards, Mark; Garfinkel, Sarah; Richardson, Mark P; Yogarajah, Mahinda
Abstract : Objectives/Aims: Patients with functional seizures (FS) can experience dissociation (depersonalisation) before their seizures. Depersonalisation encompasses a feeling of disembodiment, putatively caused by reduced afferent visceral mapping, that is, changes in interoceptive processing. The heartbeat-evoked potential (HEP) is an electroencephalographic (EEG) index of synchronised neural responses to individual heartbeats, and a marker interoceptive representation. HEP amplitude is reported to be reduced in patients with depersonalisation-derealisation disorder. The objective of this study was to assess whether alterations in interoceptive processing indexed by the HEP occur prior to FSs, and compare this with epileptic seizures (ES). Methods: HEP amplitudes were calculated from EEG during video-EEG monitoring in 25 patients with FS and 19 patients with ES, and compared between interictal and preictal states. HEP amplitudes were calculated at frontal and central EEG electrodes. HEP amplitude difference was calculated as a composite measure of preictal HEP amplitude minus interictal HEP amplitude. A Receiver Operating Characteristic (ROC) curve analysis was later used to evaluate the diagnostic performance of the HEP amplitude difference measure in discriminating functional cases from epilepsy cases. Results: The FS group demonstrated a significant reduction in HEP amplitude between interictal and preictal states at F8 (effect size rB=0.612, p=0.006) and C4 (rB=0.600, p=0.007). No differences in HEP amplitude were found between interictal and preictal states in the ES group. Between diagnostic groups, HEP amplitude difference was significantly different between the FS and ES group at C4 (rB=0.457, p=0.009) and F8 (rB=0.423, p=0.017). These findings were not related to heart rate, mean ECG or QRS amplitudes, which did not differ between interictal/preictal states, or groups. There was no difference in age between FS and ES groups, however there were a greater proportion of females compared to males in the FS group as compared to the ES group. Using HEP amplitude difference at frontal and central electrodes plus sex as variables, the ROC curve demonstrated an area under the curve (AUC) of 0.893, with sensitivity=0.840 and specificity=0.842 (p=0.000). Conclusions: Our data support the notion that aberrant interoception underpins disembodiment prior to dissociative FS. Changes in HEP amplitude may therefore reflect a neurophysiological biomarker of FS. HEP amplitude difference between interictal and preictal states may have diagnostic utility in differentiating FS and ES.